The first specimen of Archaeopteryx from the Upper Jurassic Mörnsheim Formation of Germany. (2nd January 2019) - Kundrát, Martin; Nudds, John; Kear, Benjamin P.; Lü, Junchang; Ahlberg, Per
ABSTRACT: From an initial isolated position as the oldest evolutionary prototype of a bird, Archaeopteryx has, as a result of recent fossil discoveries, become embedded in a rich phylogenetic context of both more and less crownward stem-group birds. This has prompted debate over whether Archaeopteryx is simply a convergently bird-like non-avialan theropod. Here we show, using the first synchrotron microtomographic examination of the genus, that the eighth or Daiting specimen of Archaeopteryx possesses a character suite that robustly constrains it as a basal avialan (primitive bird). The specimen, which comes from the Mörnsheim Formation and is thus younger than the other specimens from the underlying Solnhofen Formation, is distinctive enough to merit designation as a new species, Archaeopteryx albersdoerferi sp. nov., but is recovered in close phylogenetic proximity to Archaeopteryx lithographica . Skeletal innovations of the Daiting specimen, such as fusion and pneumatization of the cranial bones, well vascularized pectoral girdle and wing elements, and a reinforced configuration of carpals and metacarpals, suggest that it may have had more characters seen in flying birds than the older Archaeopteryx lithographica . These innovations appear to be convergent on those of more crownward avialans, suggesting that Bavarian archaeopterygids independently acquired increasingly bird-like traits over time. Such mosaic evolution and iterative exploration of adaptive space may be typical for major functional transitions like the origin of flight.